VOL. 2/NO.8/ NOVEMBER 2017; ISSN 2502-731X , FACTORS RELATED WITH COMPLIANCE PAYING OF BPJS MANDIRI INSURANCE/ CONTRIBUTION IN THE WORKING AREA OF BATALAIWORU PUBLIC HEALTH CENTER IN 2017 - Rismawati, Rismawati; Lisnawaty, Lisnawaty; Jufri, Nur Nashriana (Universitas Halu Oleo, 2017)
One non-beneficiary contributor is an independent worker (not a wage earner) who earns income from his ownbusiness so that when they become a participant of BPJS, they must pay contributions each month. The purposeof this study was to determine the related factors on compliance paying of BPJS Mandiriinsuranc e contribution intheworkingarea of Batalaiworupublic health centerin 2017. This research was an observational analytic with crosssectional study approach. This research was conducted in the working area of puskesmasbatalaiworu. Thepopulation in this study were all participants of BPJS Mandiri who had visitedbatalaiworu public healthcenterin2016 with a sample of 61 respondents by using simple random sampling technique. The result of the researchshows that there is a relationship between income, perception and motivation with compliance payingof BPJSMandiriinsurance contribution in the Working Area ofBatalaiworuPublic Health Centerin 2017. BPJS side shoulddevelop effort to give notification of payment of contribution to the participant through media which can reach bymajority of society, such as SMSKeywords: JKN, BPJS Mandiri, Revenue, Perception, Motivation